INDONESIAN ULAMA IN AL-HARAMAYN: A Study on the Works of al-Fâdânî and al-Bûghûrî in Musalsal Hadith - Daud Rasyid Harun; Aisyah Daud Rasyid; Muhibudin Hasan Ishak (ULUL ALBAB Jurnal Studi Islam, 2021)
The science of hadith, the accuracy factor (ḍabt) of memorization and notes, greatly determines the validity of the hadith, in addition to the trustworthiness factor of a narrator (râwî). The impact of such a strict application of the ḍabt, affects the attitudes and habits of hadith experts, such as the time, place, and special performance of the râwî. Its purpose is to further boost the accuracy of memorizing a hadith. For example, a narrator when narrating a hadith smile, then the act of smiling is also recorded by the student. He also imitates the style of his teacher smiling when narrating the hadith. This act is passed down from generation to generation, which is known as chain-related (musalsal) hadiths. However, the type of musalsal hadith does not automatically make the hadith ṣaḥîḥ. Even some musalsals are weak; some are even unauthentic. Indonesian hadith experts who studied in Mecca (al-ḥaramayn), participated in enlivening the narration and writing books on the musalsal hadiths. The names of Shaykh Yâsîn al-Fâdânî (Padang) and Mukhtâr Aṭârid al-Bûghûrî (Bogor) are listed as hadith experts from Indonesia, who have worked in the field of musalsal. The methodology used in this article is a qualitative method with descriptive approach. The article analyzes the hadiths in the works of the two hadith experts. The finding in this study is that the contribution of Indonesian hadith experts in the field of hadith is amazing, not only in the explanation (sharḥ) of hadith, but also in more detailed fields such as musalsal.